The Images of a Minister Built through the Use of Ecclesiastical Words in Emersons The Problem - Chatarina Trihastuti; Adventina Putranti (Universitas Sanata Dharma, 2014)
The Problem, a poem by Ralph Waldo Emerson, expresses Emersons preoccupation with the problem of vocation. It is about Emersons dilemma of his admiration toward church leaders despite his refusal to remain within their ranks. The Problem is analyzed from its diction -which consists of ecclesiastical words- to create images that can help the readers understand the poem. This study covers two main problems. The first is dedicated to find the meaning of the ecclesiastical words- especially those that are related to a minister- in The Problem and the second is devoted to find the images created from the ecclesiastical meanings in the previous problem.The results of this analysis show that in The Problem there are twelve expressions containing ecclesiastical meanings. The ecclesiastical meaning of a word is sometimes different from the general meaning. The ecclesiastical meaning is more specific than the general meaning. The second finding is that the ecclesiastical meanings can result in the perception of six images. The first is about the poets liking of the job of a minister and its burdens as well. The second shows that the poet would be a minister, with all of its burdens, even though he cannot see a ministers faith yet. The third is about the poets hesitance to be a minister. The fourth is that the Church with its host, chanting choir, and priest Christianize the people. The fifth is about the Bible and the prophets that teach about God and salvation. The sixth is about the poets admiration toward Chrysostom, Augustine, and Taylor and also the reason why he chose to leave the ministry.Keywords: ecclesiastical words, images